2017
DOI: 10.1371/journal.pone.0176264
|View full text |Cite
|
Sign up to set email alerts
|

ApaI polymorphism of vitamin D receptor affects health-related quality of life in patients with primary sclerosing cholangitis

Abstract: BackgroundPolymorphisms of vitamin D receptor (VDR) contribute to the pathogenesis of multiple autoimmune conditions.MethodsWe investigated the incidence of VDR polymorphisms (rs1544410-BsmI; rs7975232-ApaI; rs731236-TaqI) in a group of patients with primary sclerosing cholangitis (PSC, n = 275) and in healthy controls (n = 376). Additionally, correlations of the VDR polymorphisms with clinical and biochemical factors of the disease were analysed.ResultsThe genotype and allele distributions of these polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…The pathogenic mechanisms of genetic factors [gene polymorphisms of cytokines, growth factors, and receptors] relating chronic HCV to HCC development are not entirely well established [20]. VDR gene polymorphisms have been described in several chronic liver diseases such as liver cirrhosis [21], autoimmune hepatitis [22], primary sclerosing cholangitis [23] and primary biliary cirrhosis [24]. Moreover, it has been reported that there is a significant association between polymorphisms of VDR gene and the occurrence of HCC in alcoholic liver cirrhosis in Caucasian subjects [25], in HBV-infected patients [26] and even in patients with chronic HCV [27].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenic mechanisms of genetic factors [gene polymorphisms of cytokines, growth factors, and receptors] relating chronic HCV to HCC development are not entirely well established [20]. VDR gene polymorphisms have been described in several chronic liver diseases such as liver cirrhosis [21], autoimmune hepatitis [22], primary sclerosing cholangitis [23] and primary biliary cirrhosis [24]. Moreover, it has been reported that there is a significant association between polymorphisms of VDR gene and the occurrence of HCC in alcoholic liver cirrhosis in Caucasian subjects [25], in HBV-infected patients [26] and even in patients with chronic HCV [27].…”
Section: Introductionmentioning
confidence: 99%
“…Ten disease-specific measures included: the Short form Liver Disease Quality of Life questionnaire (LDQOL 1.0) [ 32 ]; CLDQ [ 27 , 29 , 38 , 39 , 42 , 43 ]; the NIDDK-QA [ 26 , 28 ]; Rome II Modular Questionnaire; the Cleveland Global Quality of Life questionnaire (CGQOL) [ 34 ]; the Short Inflammatory Bowel Disease Questionnaire (SIBDQ) [ 32 , 47 ]; Oresland scale; PSC PRO; [ 43 ] PBC-27 [ 35 , 40 , 41 ]; and PBC-40 [ 32 , 35 , 40 , 41 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the studies we identified, a raised serum alkaline phosphatase was linked to worsened mental health. 12 The presence of Apa-I polymorphism of vitamin D receptors was found to be associated with poorer quality of life, mental-and emotional-healthrelated scores 60 Finally, the other two existing studies found that neither serum autotaxin nor plasma tyrosine concentrations affected mental health or quality of life. 61,62…”
Section: Theme 4: Medical Treatmentmentioning
confidence: 94%